Caregiver Experience in Potty Training Children with Down Syndrome - Purnamawati, Rifka; Shaluhiyah, Zahroh; Suryoputro , Antono (Jurnal Ilmu Kesehatan Masyarakat, 2023)
Potty training assistance for children with Down syndrome is challenging because it takes longer to adapt and has physical and cognitive limitations. In addition, educating children with Down syndrome differs from one child to another. The study aimed to explore the role of parents or caregivers in teaching the potty training process to children with Down syndrome at States Special Needs School Semarang. The research was conducted using a qualitative phenomenological approach to determine parental participation in potty training in children with Down syndrome. Data collection was carried out by in-depth interviews and observations supplemented by field notes which were then transcribed verbatim. The search for informants used a purposive sampling method selected based on specific considerations with a total of 10 primary informants and those who cared for children with Down syndrome aged 7-14 years and were still in elementary school and two triangulated informants from teachers. Data analysis was carried out thematically. The results of the study found that the knowledge of most caregivers about potty training was limited to taking their children to the toilet, most of the children with Down syndrome were unable to urinate independently, the caregiver’s difficulties when teaching potty training were problems communicating with the child, the caregiver’s task in the potty training process was as follows: by finding solutions to make it easier for children to communicate and understand children’s conditions. This qualitative research concludes that there is a theme regarding the role of caregivers with Down syndrome in potty training: caregiver knowledge about potty training, the behavior of children with Down syndrome during potty training, caregiver difficulties in potty training, and the caregiver’s role or task in potty training.